Non-fatal injuries in three Central and Eastern European urban population samples: the HAPIEE study - Vikhireva, Olga; Pikhart, Hynek; Pajak, Andrzej; Kubinova, Ruzena; Malyutina, Sofia; Peasey, Anne; Topor-Madry, Roman; Nikitin, Yuri; Marmot, Michael; Bobak, Martin (European journal of public health, 2010)
BACKGROUND: Despite high mortality from injuries and accidents, data on rates and distribution of non-fatal injuries in Central and Eastern European populations are scarce. METHODS: Cross-sectional study of random population samples of 45-69-year-old men and women (n = 28 600) from Novosibirsk (Russia), Krakow (Poland) and six Czech towns, participating in the Health, Alcohol and Psychosocial factors In Eastern Europe (HAPIEE) study. Participants provided information on non-fatal injuries in the past 12 months, socio-economic characteristics, alcohol consumption and other covariates. RESULTS: The period prevalence of non-fatal injuries in the last year among Czech, Russian and Polish men was 12.5, 9.4 and 5.3%, respectively; among women, the respective proportions were 9.9, 9.8 and 6.4%. Injury prevalence declined with age in men and increased with age in women. Higher injury prevalence was associated with being unmarried, material deprivation, higher drinking frequency and problem drinking. In the pooled data, the adjusted odds ratio (OR) for the highest versus lowest material deprivation category was 1.57 [95% confidence interval (CI) 1.38-1.79]; for problem drinking, the OR was 1.44 (95% CI 1.23-1.69). Alcohol did not mediate the link between socio-economic status and injury. CONCLUSION: Non-fatal injuries were associated with material deprivation, other socio-economic characteristics and with alcohol. These results not only underscore the universality of the inequality phenomenon, but also suggest that the mediating role of alcohol in social differentials in non-fatal injury remains an unresolved issue.
Keywords: Socioeconomic Factors; Russia; Cross-Sectional Studies; Alcoholism; Comorbidity; Male; Risk Factors; alkoholismus; Poland; Česká republika; Urban Population; prevalence; rozložení podle pohlaví; socioekonomické faktory; Aged; Wounds and Injuries; mužské pohlaví; senioři; Sex Distribution; disparity zdravotního stavu; komorbidita; Czech Republic; lidé; ženské pohlaví; Humans; Health Status Disparities; Psychosocial Deprivation; rizikové faktory; průřezové studie; Rusko; Prevalence; Age Distribution; věkové rozložení; rány a poranění; Female; Polsko; psychosociální deprivace; lidé středního věku; městské obyvatelstvo; Middle Aged